2016
DOI: 10.14474/ptrs.2016.5.4.198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hip joint exercise using an elastic band on dynamic balance, agility and flexibility in healthy subjects: a randomized controlled trial

Abstract: Objective: The purpose of this study was to examine the effects of hip joint exercise using an elastic band on dynamic balance, agility, and flexibility in healthy subjects. Design: Randomized controlled trial. Methods: Thirty-five subjects (between 19 and 23 years) were randomly allocated to two groups: hip flexion exercise (HFE) group (n=17) and the hip abduction exercise (HAE) group (n=18). The HFE group participated in flexion exercise of the hip joint using an elastic band for 50 minutes a day, three days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it was found that it is necessary to move the load to the leg muscles by lowering the wearing height in order to reduce fatigue and pain of the ES muscles when wearing the baby carrier anteriorly. In addition, the ES muscles appear to require greater muscle activity during the trunk extension compared to flexion, and it seems necessary to distribute the load to be applied to the passive structures of the vertebral muscles and lower back through the adjusted leg movement during the trunk flexion and extension [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was found that it is necessary to move the load to the leg muscles by lowering the wearing height in order to reduce fatigue and pain of the ES muscles when wearing the baby carrier anteriorly. In addition, the ES muscles appear to require greater muscle activity during the trunk extension compared to flexion, and it seems necessary to distribute the load to be applied to the passive structures of the vertebral muscles and lower back through the adjusted leg movement during the trunk flexion and extension [27].…”
Section: Discussionmentioning
confidence: 99%